TIMP-3 is a potent inhibitor of aggrecanase 1 (ADAM-TS4) and aggrecanase 2 (ADAM-TS5). - Kashiwagi, M; Tortorella, M; Nagase, H; Brew, K (2001)
The proteoglycan aggrecan is an important major component of cartilage matrix that gives articular cartilage the ability to withstand compression. Increased breakdown of aggrecan is associated with the development of arthritis and is considered to be catalyzed by aggrecanases, members of the ADAM-TS family of metalloproteinases. Four endogenous tissue inhibitors of metalloproteinases (TIMPs) regulate the activities of functional matrix metalloproteinases (MMPs), enzymes that degrade most components of connective tissue, but no endogenous factors responsible for the regulation of aggrecanases have been found. We show here that the N-terminal inhibitory domain of TIMP-3, a member of the TIMP family that has functional properties distinct from other TIMPs, is a strong inhibitor of human aggrecanases 1 and 2, with K(i) values in the subnanomolar range. This truncated inhibitor, which lacks the C-terminal domain that is responsible for interactions with molecules other than active metalloproteinases, is produced at high yield by bacterial expression and folding from inclusion bodies. This provides a starting point for developing a biologically available aggrecanase inhibitor suitable for the treatment of arthritis.